Role of organisational culture on performance measurement practice: the case of Malaysian manufacturing firms - Mohamad, Muslim Har Sani; Ali, Fazlin; Mohd Amir, Amizawati (Inderscience Publishers, 2013)
Abstract: This study aims to examine the influence of the competing values on firm performance mediated by diverse performance measurement system. With a different focus to that of Henri’s (2006) concept of dominant culture, we argue that in control dominant firms, flexibility and diverse performance measures (PM) can lead to improved performance. Testing of the two competing values based on dominant culture exclude the chance to test this possibility. Also, we propose that through the use of diverse PM, the flexibility value of the firms will have stronger influence on firms’ performance than the control values. As the most developed sector in Malaysian economy, manufacturing companies need to adopt the right mix of PMs to be competitive in facing globalised market, thus, they were selected for the study. The study found that with stronger presence of cogent leadership, use of diverse performance measures can translate flexibility values into firms’ improved performance.